PELAKSANAAN BIMBINGAN KARIER UNTUK KEMANDIRIAN SISWA TUNARUNGU DI SMALB - AISAH DHARMA, SENJA (Jurnal Pendidikan Khusus, 2015)
ABSTRACT            Career guidance is a service process for child have the need of special in order to child gets the picture he/she, recognize education types, and recognize [job/activity] world until from information – information that obtained/got expected can take choice and take a decision in accordance with it-self situation. In this research career guidance execution for independence is career guidance service that has been executed or executed in accordance with systematic guidance of career guidance execution cover supervisor approach, technique of individual understanding, technique and approach way, and technique of evaluation to student independence of deaf so that can create independence in conducted job either when career guidance execution or independence that have been formed after career guidance execution. Systematic and optimal career guidance Execution is expected will have an in with student independence of deaf in taking choice after graduate from SMALB in accordance with enthusiasm and talent. In career guidance execution existed constraint factor that can pursue process of career guidance execution. In consequence,, the party of school must give solution to overcome constraint factor that can pursue process of career guidance execution and shall always improve effectiveness implementation career guidance in order to student of deaf more self-supporting in takes correct decision to select its career. Research Target this is the for describe execution, constraint factor, and solution in overcoming career guidance constraint for student independence of deaf in SMALB-B Karya Mulia Surabaya. This Research uses method descriptive with approach qualitative. Base analysis of research data is obtained/got research result that career guidance execution have been executed properly, that thing proven by available its guidance of career guidance execution that systematics in SMALB-B Karya Mulia Surabaya. Brief Guidance career guidance execution is referred [as] cover supervisor approach, technique of individual understanding, technique and approach way, and technique of evaluation. In every constraint factor that pursue career guidance execution, the party of school can give best solution to overcome constraint factor is referred [as]. The party of school also always conducted service repair in optimize career guidance execution, proven from new program that will be executed called “Planning Extra magpie” that is visit to place that more complete in accordance with skill majors that taken.   Keyword    : Career guidance, Independence